Design and efficiency testing of a prototype extruder for Bang Kaew dog food production - Phasinam, Thanwamas; Incharoen, Tossaporn; Nualsri, Chatchawin; Watcharinrat, Dowroong; Phasinam, Khongdet (Journal of Asian Scientific Research, 2024)
This research aims to address this issue by designing and fabricating a prototype extruder specifically tailored for producing Bang Kaew dog food. The Bang Kaew dog breed, native to Thailand, poses a challenge for farmers seeking cost-effective dog food production using locally available ingredients. Despite attempts to minimize expenses, the necessity of machinery in pellet formation remains, contributing significantly to production costs. The study comprises two main phases: designing and fabricating the extruder machine and testing its efficiency for Bang Kaew dog food production. The extruder, a single screw machine, measures 380 x 810 x 345 millimeters and operates on 220 volts, consuming 2200 watts of power. After rigorous testing, the optimal extruder speed for Bang Kaew dog food production was found to be 400 rpm, achieving a production capacity of 136.29 kilograms per hour and a maximum efficiency of 74 percent. The produced dog food exhibited a moisture content of 9.01 percent and specific color values (L*=72.18±1.75, a*=2.60±0.22, b*=14.35±0.41). Additionally, the hardness measured 272.82 Newton, and the water activity (aw) was 0.67. Significantly, the physical characteristics of the dog food produced at 400 rpm closely resembled those of commercial dog food. This study showcases the successful development of an efficient extruder machine tailored for Bang Kaew dog food, providing valuable insights for the pet food industry.